2005
DOI: 10.1002/adma.200500508
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission of Electrons from Single LaB6 Nanowires

Abstract: ing in a bending of the AFM cantilever and an increase in the shear stress at the interface. The cantilever bending increased until the force applied to the nanotube was sufficient to pull the nanotube from the polymer ( Fig. 1) owing to interfacial failure in shear. This test was repeated using larger nanotube embedded lengths by pushing the nanotube at different depths into the liquid. The embedded lengths were evaluated from SEM images of the nanotube before and during embedment within the epoxy. Further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 25 publications
3
109
0
1
Order By: Relevance
“…[31,[33][34][35] The Fowler-Nordheim (FN) equation is used to describe the metal-vacuum field-emission model, in which good linearity of the FN plots means the cathode material agrees with this model and is close to the behavior of metal. The typical FN plot, ln(I/ E 2 ) versus 1/E, is shown in Figure 5C.…”
Section: Figure 2 A) a Typical Tem Image Of The Bnws B) A Hrtem Imamentioning
confidence: 99%
“…[31,[33][34][35] The Fowler-Nordheim (FN) equation is used to describe the metal-vacuum field-emission model, in which good linearity of the FN plots means the cathode material agrees with this model and is close to the behavior of metal. The typical FN plot, ln(I/ E 2 ) versus 1/E, is shown in Figure 5C.…”
Section: Figure 2 A) a Typical Tem Image Of The Bnws B) A Hrtem Imamentioning
confidence: 99%
“…[10][11][12][13][14][15] Thus, 1D LaB 6 nanostructures should be an ideal candidate for FE applications, especially if LaB 6 nanostructures have an elongated geometry and sharp emitting tips. Zhang et al 10 have demonstrated room temperature (RT) FE of a single LaB 6 nanowire with a current density as high as 5 Â 10 5 A cm À2 at a working voltage of 800 V, which is one order of magnitude higher compared with that of the state-of-the-art W/ZrO thermal field emitters working at 1800 1C with a 3-kV extraction voltage. An individual LaB 6 nanowire also shows an emission current density comparable to that of an individual C nanotube with a diameter 10-50 times smaller.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used in wear and corrosion resistant hard coatings for decoration of consumer products such as eye-glass frames and wristwatch casings (Mitterer et al, 1996;Selvan et al, 2008). Single crystalline LaB 6 nanowires are one of the most widely used electron emitter in electron gun, which can offer about 10 to 15 times higher brightness, higher emission stability, lower energy spread and longer service life than the tungsten cathodes utilized in a large variety of devices such as high-resolution electron microscopes, electron beam writing units, vacuum electron beam welding machines, microwave tubes, free electron lasers, X-ray tubes, electron beam surface reforming and electron beam lithography devices (Ahmed et al, 1975;Perkins et al, 1999;Chen et al, 2004;Wen et al, 2004;Zhang et al, 2006Zhang et al, , 2007Wang et al, 2009;Qin et al, 2010;Bao et al, 2011). Moreover, LaB 6 nanomaterials are candidates to motivate the new designs of nanoscale electronic devices operated at high temperatures with the need of enhanced electron collection and injection properties (Brewer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…SHS methods have high reaction speed, simple equipment and low energy consumption but after ignition, the reaction process becomes uncontrolled which results in the occurrence of intermediate phases in the reaction products (Dou et al, 2011). LaB 6 whiskers, wires, tubes and obelisks in nano-or micro-scales have been produced by chemical vapor deposition technique (CVD) (Motojima et al, 1978;Zhang et al, 2006). CVD methods include self-catalyst or metal-catalyst (Au, Pt, etc.)…”
Section: Introductionmentioning
confidence: 99%